KEPUTUSAN TATA USAHA NEGARA MENURUT UNDANG-UNDANG PERADILAN TATA USAHA NEGARA DAN UNDANG-UNDANG ADMNISTRASI PEMERINTAHAN - Dola Riza (Jurnal Bina Mulia Hukum, 2018)
ABSTRAK KTUN sebagai objek sengketa di PTUN telah diatur dalam UU PTUN termasuk prosedurnya. Setelah diundangkannya UU AP, KTUN dan prosedurnya ini juga turut diatur dalam UU AP, namun terdapat perbedaan dalam pengaturan terhadap hakikat keputusan dan prosedurnya. Jenis penelitian yang digunakan adalah penelitian hukum normatif dengan menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Penelitian ini menggunakan bahan hukum primer, sekunder dan tersier. Teknik pengumpulan bahan hukum yang digunakan adalah studi dokumen dengan teknik analisis kualitatif. Berdasarkan hasil penelitian dapat disimpulkan bahwa terdapat perbedaan pengaturan terhadap 3 aspek yang diatur dalam UU PTUN dan UU AP, yaitu pertama pengaturan terhadap hakikat KTUN, kedua pengaturan terhadap status permohonan yang didiamkan oleh Badan dan/atau Pejabat TUN, ketiga pengaturan terhadap pengajuan gugatan yang melalui upaya administratif berupa banding. Meskipun terdapat perbedaan, pengaturan untuk hukum materil berpedoman kepada UU Administrasi Pemerintahan dan hukum formil tetap berpedoman kepada UU PTUN. Implikasi dari Pengaturan terhadap hakikat KTUN dalam UU PTUN dan UU AP adalah terjadinya perluasan kriteria KTUN dan perluasan kewenangan PTUN. Kata kunci: administrasi pemerintahan; keputusan TUN; sengketa. ABSTRACT Decision of State Administration as the object of dispute in the state administrative court has been regulated in the statutory administrative law of the state including its procedures. After the promulgation of the law of the Government Administration, The state administrative decisions and procedures are also governed by the laws of the Government Administration. but there are differences in the arrangement of the nature of decisions and procedures. Type of research used is normative legal research with used is approach to legislation and conceptual approaches. The legal material used is primary, secondary and tertiary legal materials. The technique of collecting the legal material used is study documents with used qualitative analysis techniques. Based on the results of the study can be concluded that 1). there are different settings against the 3 aspects set forth in laws of state administrative courts and government administration laws that is, the first is the regulation of the nature of the state administrative decisions, the second is the regulation of the status of the government’s silenced petition, third is the arrangement of a lawsuit filed through an administrative appeal in the form of an appeal, Although there are differences, arrangements for material law are guided by the laws of the Government Administration and formal law remains guided by the state administrative court law. 2). Implications of Arrangements on the nature of state administrative decisions in state administrative justice laws and Government Administration laws are the occurrence of expansion of the criteria of state administrative decisions and expansion of the authority of the state administrative court. Keywords: goverment administration; decision of state administration; dispute.